Between Point Zero and the Iron Curtain : International Cooperation in Art and the Postwar Moment, 1945-1948 - Forgács, Éva, (Avant-Garde Critical Studies ;, 2025)
This volume, edited by Éva Forgács, with contributions from art historians from across Europe and the Americas, analyzes the artistic initiatives of the short time span between the end of World War II and the onset of the Cold War. In this moment, a new internationalism was anticipated by retrieving pre-war modernism, as well as creating the new era's new artistic lingua franca. The chapters include in-depth case studies that analyze the complex, often interconnected, projects throughout the world-South America, North Africa, and eastern and western Europe-that were soon ended by the Cold War. See Less